2019
DOI: 10.1002/lno.11341
|View full text |Cite
|
Sign up to set email alerts
|

Response of small sharks to nonlinear internal waves

Abstract: Plankton and nekton may respond passively or actively to large-amplitude, nonlinear internal waves (NLIW), with periods and wavelengths on the order of minutes and hundreds of meters, and the NLIW can cause direct or indirect changes in distribution. NLIW are ubiquitous in the coastal ocean, but understanding the influence of NLIW on organism response and distribution is challenging, because of NLIW unpredictability, short temporal and spatial scales, and the difficulty in resolving the biological response. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…In summary, our results show that internal seiche events in lakes can drive the vertical positioning of fish. This observation builds upon other studies that also found fish in different thermally stratified systems also respond to internals waves (Levy et al 1991;Pineda et al 2020;Flood et al 2021b). The compression of walleye into oxygen-rich and warm epilimnetic waters will increase their metabolic demand, therefore requiring an increase in prey biomass for sustenance.…”
Section: Discussionsupporting
confidence: 85%
“…In summary, our results show that internal seiche events in lakes can drive the vertical positioning of fish. This observation builds upon other studies that also found fish in different thermally stratified systems also respond to internals waves (Levy et al 1991;Pineda et al 2020;Flood et al 2021b). The compression of walleye into oxygen-rich and warm epilimnetic waters will increase their metabolic demand, therefore requiring an increase in prey biomass for sustenance.…”
Section: Discussionsupporting
confidence: 85%
“…Estimation of turbulent mixing on the continental shelf is important for understanding the structure and dynamics of marine ecosystems, nutrient cycling, primary production and dispersion of pollutants (Nash et al, 2004;Pineda et al, 2020;Rippeth et al, 2005;Schafstall et al, 2010). Diapycnal mixing in the ocean is mostly driven by intermittent patches of small-scale turbulence (Müller and Briscoe, 2000).…”
Section: Internal Waves and Diapycnal Mixing In The Coastal Oceanmentioning
confidence: 99%
“…Physical processes, such as IWs, can be observed via spatial and temporal variations in zooplankton layers, whose acoustic responses vary, according to their observed frequency and which are visible with low acquisition thresholds (no more than -80 dB based on the assumption of a backscatter around -70/-75 dB for the zooplankton layers) (Bertrand et al, 2010;Pineda et al, 2020). Furthermore, Sandstrom et al (1989) indicated that acoustic backscatter levels in turbulent patches approach -50 dB at 200 kHz, providing a rapid and convenient survey tool for estimating mixing levels induced by IWs.…”
Section: Echosounder (Ek60)mentioning
confidence: 99%
“…Small‐scale pelagic habitat heterogeneities are associated with physical convergent and divergent processes, such as estuarine fronts, with surface across‐front hydrographic gradients (Govoni & Grimes, 1992; O'Donnell et al, 1998) and internal waves (Alpers, 1985), with generally no surface hydrographic variability (but see Pineda et al, 2020, for highly nonlinear internal waves). Mixing can modulate the erosion of small‐scale heterogeneities (O'Donnell, 1990), but upper layer mixing by strong winds (>10 m/s) and surface waves can also be associated with convergent and divergent Langmuir circulation (Kukulka et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Small-scale pelagic habitat heterogeneities are associated with physical convergent and divergent processes, such as estuarine fronts, with surface across-front hydrographic gradients (Govoni & Grimes, 1992;O'Donnell et al, 1998) and internal waves (Alpers, 1985), with generally no surface hydrographic variability (but see Pineda et al, 2020, for highly nonlinear internal waves).…”
Section: Introductionmentioning
confidence: 99%